Power Aware Simulation Challenges and Solutions in Semiconductor ICs Design Verification - Nilesh Patel (International Journal of Intelligent Systems and Applications in Engineering, 2021)
Power-aware design verification has become a critical aspect of modern integrated circuit (IC) development, especially in the context of low-power, high-performance applications such as mobile devices, IoT systems, and automotive electronics. With the increasing demand for energy efficiency, design engineers must ensure that power intent is accurately captured, implemented, and verified across various design abstraction levels. However, verifying power-aware designs introduces several unique challenges. These include ensuring correct functionality across multiple power domains, managing power state transitions, verifying retention and isolation strategies, and detecting unintended power-induced bugs such as data corruption or signal contention. One of the major challenges is the lack of a unified methodology to validate both functional and power intent cohesively. Traditional verification flows often fall short in identifying subtle power-related issues due to the complexity of power-aware features like Multi-Voltage Domains (MVD), Power Gating, and Dynamic Voltage and Frequency Scaling (DVFS). Moreover, integrating power-aware simulations with functional verification environments requires careful coordination between Unified Power Format (UPF) or Common Power Format (CPF) specifications and RTL design. To address these issues, several solutions have been proposed and adopted in the industry. These include the use of formal verification techniques for exhaustive state-space analysis, dynamic simulation with power-aware testbenches, and automated rule-checking tools that validate UPF/CPF semantics against RTL. Assertion-based verification (ABV) and low-power aware test scenarios also play a crucial role in ensuring coverage of power-related corner cases. Additionally, emulation and hardware-assisted verification provide scalable solutions for large SoCs where simulation falls short. In conclusion, power-aware design verification demands a multi-faceted approach that combines formal, dynamic, and static techniques. The evolution of EDA tools and methodologies tailored to power-aware verification is key to enabling robust, low-power IC designs in today’s competitive semiconductor landscape.